(untitled) (Ustozlar uchun, 2026)
The 21st century faces a multifaceted ecological crisis characterized by rapid climate change and systemic environmental degradation. This article explores the causal links between industrial waste, greenhouse gas emissions, and the collapse of natural ecosystems. Central to this discussion is the role of recycling—not merely as a waste management tool, but as a fundamental pillar of a circular economy. The study analyzes how sustainable resource management can mitigate carbon footprints and proposes a shift from linear consumption to systemic sustainability.